2006
DOI: 10.1021/es061649s
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Dependence of Fe(II) Photoformation in the Water-Soluble Fraction of Aerosols Collected in Okinawa, Japan

Abstract: We studied photoformation of Fe(II) in the water-soluble fractions (WSFs) of bulk aerosol particles collected in Okinawa, Japan, using radiation at wavelengths of 313, 334, 366, and 405 nm. Fe(II) photoformation quickly reached a steady state within 5 min of irradiation at all wavelengths. The steady-state Fe(II) concentrations were 85+/-13% (n = 39) of the total dissolved Fe (TDFe) concentrations in the WSF solutions. Apparent quantum yields of Fe(II) photoformation were determined based on total absorbance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Our study reveals that high level of Fe(II)/Fe(t) (Figure ) can be maintained for a long time in the presence of excess Mal. Many field measurements indicated that Fe(II) accounts for most of the dissolved iron in rainwaters ,, , but the mechanism involved for (photo)stability of Fe(II) is unclear . It is of interest to totally identify the dissolved organic matters in rainwaters, particularly dicarboxylic acids, to understand the speciation of dissolved iron in carbon-rich troposphere, although the correlation of Mal with Fe(II) against (photo)oxidation in rainwater remains obscure so far because rainwater may have high concentrations of other oxidants generated via non metal redox pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Our study reveals that high level of Fe(II)/Fe(t) (Figure ) can be maintained for a long time in the presence of excess Mal. Many field measurements indicated that Fe(II) accounts for most of the dissolved iron in rainwaters ,, , but the mechanism involved for (photo)stability of Fe(II) is unclear . It is of interest to totally identify the dissolved organic matters in rainwaters, particularly dicarboxylic acids, to understand the speciation of dissolved iron in carbon-rich troposphere, although the correlation of Mal with Fe(II) against (photo)oxidation in rainwater remains obscure so far because rainwater may have high concentrations of other oxidants generated via non metal redox pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Although an estimate of aerosol transport time was not given, Zhuang et al (1992) found that significant conversion between Fe(II) and Fe(III) can occur during transport, with reduction of Fe(III) to Fe(II) being more significant than oxidation of Fe(II) to Fe(III) in marine aerosols. A number of studies have sought to measure the rates of photoreduction of Fe(III) in aqueous leaches or suspensions of aerosols (Okada et al, 2006;Zhu et al, 1993). These studies found that, in the leachate, the Fe(II) levels quickly increase upon irradiation of the aerosol solution, with the levels reaching a pseudo steady-state within 45 min.…”
Section: >25 µMmentioning
confidence: 99%
“…Barbeau et al reported the key features of the iron cycle involving photolysis of Fe(III)–ligand complexes, with reduction of Fe(III) to Fe(II) and oxidation of the ligand. The wavelength dependence and quantum yields of Fe(II) photoformation in aerosol particles have been studied, and the results had implications to daytime Fe(III)/Fe(II) cycles in the atmospheric liquid phase . Zhao et al observed a regular oscillation in the ratio of Fe(II) to total iron when dissolved organic matter (DOM) was periodically added into the solution under irradiation.…”
Section: Introductionmentioning
confidence: 99%